50 pī Sathāban Wičhai Phrưttikammasāt "lǣ lang mung wang sū ʻanākhot" prawat phonngān botkhwām wichākān (Sathāban Wičhai Phrưttikammasāt, Mahāwitthayālai Sīnakharinwirōt, 2005)
Research and academic work during the past fifty years of the Behavoiral Science Research Institute at Srinakharinwirot University.